Economies of Scale in the Administration of Health Insurance - Blair, Roger D.; Jackson, Jerry R.; Vogel, Ronald J. (The Review of Economics and Statistics, 1975)
W HILE debate rages on, it seems only a matter of time before some form of national health insurance becomes a reality. Aside from the central questions regarding coverage, financing, and eligibility, an important issue involves the administration of such an insurance program. A recent analysis of 13 proposed national health insurance bills found that 10 of the bills include the existing industry to one degree or another.' This strategy makes sense because of the expertise and machinery that presently exist within the health insurance industry. If such a strategy is adopted, the fundamental problem of allocating the administrative responsibility remains. There is wide disparity in the average costs of administration among the insuring organizations. Ideally, designation of responsibility for administering any national health insurance program should be based upon efficiency considerations. To the extent that economies of scale are present within the administrative function of existing health insurers, centralization in one or a few hands can be justified. In contrast, if economies of scale are not present, administrative responsibility should be decentralized on efficiency grounds. The purpose of the present paper is to examine the administrative cost experience of the commercial health insurers in an effort to determine whether economies of scale exist.